Comparison of Breakdown Voltage and Aging of Kraft Paper in Transformers Immersed in Mineral Oil, Natural Ester, and Synthetic Ester - Hanifiyah Darna Fidya Amaral; Galuh Prawestri Citra Handani; Rahman Azis Prasojo; Reyhan Fadhlur Rahman; Satria Lutfi Hermawan; Ruwah Joto; Afidah Zuroida; Ahmad Hermawan; Irwan Heryanto/Eryk (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
Transformers are critical components in electrical power systems that rely on insulation oil and paper to ensure reliable and long-lasting operation. This study aims to compare the performance of kraft insulation paper immersed in three types of transformer oil, namely mineral oil, natural ester, and synthetic ester, through the accelerated thermal aging method. Evaluation was carried out based on tensile strength and water content testing in accordance with the IEEE C57.100-2011 standard, as well as breakdown voltage testing in accordance with the IEC 60156-2018 standard. Tests were conducted with samples taken at intervals of 24, 240, 480, and 720 hours at 150°C. The results showed that insulation paper soaked in mineral oil experienced a 34% decrease in tensile strength, while natural ester and synthetic ester oils showed tensile strengths of 66% and 52%, respectively. In the water content test, natural ester showed the best performance with the lowest water content (5.19%), followed by mineral oil (7.47%) and synthetic ester (46.70%). In the breakdown voltage test, natural ester had the highest breakdown voltage of 66.26 kV, followed by mineral oil at 63.96 kV and synthetic ester at 41.14 kV. Estimated insulation life based on lifetime regression showed that natural ester has a lifetime of up to 37.9 years, synthetic ester 25.6 years, and mineral oil 20.5 years. In addition, in transformers operating at 130°C, natural ester insulation oil can increase loading up to 20% higher than mineral oil and has a 15-20°C higher operating temperature. This study recommends the use of kraft insulation paper impregnated with natural ester and synthetic ester oils as an alternative to mineral oil, because both are superior environmentally friendly alternatives compared to mineral oil. Both oils have better mechanical strength and insulation, lower water content, and can slow down transformer aging. Furthermore, these ester oils are non-flammable, biodegradable, and reduce the risk of failure due to excessive heat or discharge, thereby increasing the reliability and lifespan of the transformer. With these properties, ester oils support safer and more sustainable operations for the power system.